Pancreatic Cancer With Special Focus on Topical Issues and Surgical Techniques - Kim, Sun-Whe.; Yamaue, Hiroki; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides state of the art knowledge on a broad range of clinical issues in pancreatic cancer, covering topics from screening and pathophysiology to surgical treatments. In particular, the focus is on current controversies and on evidence-based surgical techniques. Further aspects considered include the management of precancerous lesions, diagnostic methods, perioperative care and nonsurgical treatment. The description of surgical methods is supported by many helpful illustrations and important technical issues are carefully addressed. Determination of resectability and extent of surgery is also discussed. Based on recent developments in surgical techniques, some surgeons are performing more and more radical operations. It is essential, however, that surgical strategy is based on the best available evidence and surgeons will find that this book offers valuable help in achieving this aim. In addition, it will be a great asset in clinical practice for all who are involved or interested in the management of pancreatic cancer.
1. Pathology & Tumor biology -- Epidemiology -- Genetic background & hereditary pancreatic cancer -- Pathological classification -- Tumor biology (precancerous lesion and mode of spread) -- Current update/controversial issue -- Specimen handling & margin status -- Tumor marker -- 2. Diagnosis -- CT, MRI -- Endoscopic diagnosis -- PET -- Current update/controversial issue -- Functional imaging for pancreatic neoplasms (including PNET) -- 3. Treatment guideline -- Staging and determination of resectability of pancreatic cancer -- Guideline for the management of other pancreatic neoplasm -- IPMN & MCN -- SCN -- pNET -- Current update/controversial issue -- Definition of borderline resectable PDAC -- Role of neoadjuvant treatment -- 4. Surgery -- Technical issues in surgery -- Conventional Pancreatoduodenectomy -- Vessel Resection for PDAC (type & technique) -- Nerve plexus dissection -- Organ preserving pancreatectomy -- Type of Reconstruction -- Isolated pancreatectomy -- Mesenteric vessel first approach -- DP-CAR -- RAMPS -- Minimal invasive pancreatectomy -- Laparoscopic Pancreatoduodenectomy -- Laparoscopic distal pancreatectomy -- Roboticapplication for pancreatectomy -- Current update/controversial issue -- Role of extended resection for PDAC -- Concept of customized surgery -- 5. Morbidity and perioperative care -- Pancreatic fistula -- Delayed emptying -- Postoperative bleeding -- Other rare complication -- Late metabolic complication -- Current update/controversial issue -- ERAS -- Drain care after pancreatoduodenectomy -- 6. Nonoperative therapy for pancreatic cancer -- Adjuvant therapy -- Palliative chemotherapy. - Radiation therapy.
Keywords: Medicine; Radiology; Pathology; Surgery; Medicine & Public Health; Surgery; Diagnostic Radiology; Pathology